Meta-Path Augmented Response Generation - Li, Yanran; Li, Wenjie (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We propose a chatbot, namely MOCHA to make good use of relevant entities when generating responses. Augmented with meta-path information, MOCHA is able to mention proper entities following the conversation flow.